“Seeing the World with Fresh Eyes” - Seamon, David (Religion and the arts, 2017)
In this article, I draw on Gurdjieff’s philosophy to initiate a phenomenology of aesthetic experience, which I define as any intense emotional engagement that one feels in encountering or creating an artistic work, whether a painting, poem, song, dance, sculpture, or something else. To consider how aesthetic experience might be understood in a Gurdjieffian framework, I begin with an overview of phenomenology, emphasizing the phenomenological concepts of lifeworld and natural attitude, about which Gurdjieff said much, though not using phenomenological language. I then discuss Gurdjieff’s “psychology of human beings” as it might be interpreted phenomenologically, emphasizing three major claims: first, that, human beings are “asleep”; second, that they are “machines”; and, third, that they are “three-centered beings.” I draw on the last claim—human “three-centeredness”—to highlight how aesthetic experiences might be interpreted via Gurdjieff’s philosophy. Drawing on accounts from British philosopher and Gurdjieff associate J. G. Bennett, I end by considering how a Gurdjieffian perspective understands the role of the artistic work in contributing to aesthetic experience.